Optical Frequency Domain Reflectometry: Sensing Range Extension and Enhanced Temperature Sensitivity - Song, Jia (Université d'Ottawa / University of Ottawa, 2014)
Optical fiber sensors have attracted tremendous attention over last two decades and have been successfully employed in various sensing applications, including temperature, strain, current, and so on. Among all types of optical fiber sensors, optical frequency domain reflectometry (OFDR) has been widely studied for its merits of simple configurations, high spatial resolution and high sensing accuracy. However, current limitation on OFDR lies in the sensing range and sensing accuracy. The state of art performance of commercial OFDR provides ~70m sensing range as well as 0.1K temperature accuracy. This is not adequate for large building distributed health monitoring due to the limited sensing range. Besides, high temperature response is also on demand for high precision measurement. To resolve the above limitation, in this thesis two major subjects have been studied regarding improving the performance and applicability of OFDR: One aims at extending the sensing range of OFDR while the other one focuses on enhancing temperature sensitivity of OFDR. Firstly, we proposed novel data resampling approach regarding tuning nonlinearities of laser source to extend the sensing range. Commercial OFDR employs auxiliary interferometer (AI) to trigger data acquisition, where the maximum sensing range is limited to a quarter of the optical path difference (OPD) of AI according to Nyquist Sampling theorem. By employing the data resampling algorithm, the sensing range is no longer restricted by OPD and can even reach laser coherent length since OFDR is based on coherent detection scheme. Three data resampling algorithms are individually discussed and a sensing range of ~300m (~4 times the sensing range of commercial OFDR) with 8cm spatial resolution is for the first time achieved. Secondly, the temperature response of OFDR is enhanced and we successfully achieved high temperature accuracy distributed sensing. One advantage of high temperature response is to enhance the spatial resolution since less spatial points are required in performing cross-correlation, while the other advantage is to obtain high temperature accuracy measurement at the same spatial resolution compared to that of traditional OFDR. This is especially important for maintaining spatial resolution under long range OFDR sensing since the total wavelength tuning range is smaller than traditional OFDR. Commonly the temperature response of single mode fiber is contributed by both thermal expansion coefficient and thermal optic coefficient of the waveguide and can be enhanced by increasing either of those coefficients. Thermal expansion coefficient is related with material property and is a weighted value of both bare fiber and coating. By using a large thermal expansion coefficient acrylic plank as a “coating” on SMF, we achieved ~9 times temperature response (~95 pm/ ˚C) compared with SMF (~10 pm/ ˚C). Further experiment is demonstrated with small diameter taper on an acrylic plank “coating”, in which case both thermal expansion coefficient and thermal optic coefficient are raised and a ~20 times temperature response than SMF (~200 pm/˚C) is obtained. This is especially meaningful for its easy fabrication, low cost and extremely high temperature response and leads to practical usage for high accuracy distributed temperature sensing.
Keywords: Fiber; Optics; Sensing